Naringenin modifies T-helper responses and macrophage activities in BALB/c mice - Fatemeh Keivan; Seyyed Meysam Abtahi Froushani (Mashhad University of Medical Sciences, 2024)
Objective: Naringenin is a naturally occurring flavonoid found in citrus fruits. This study was done to compare the oral immunomodulatory effects of naringenin and prednisolone. Materials and Methods: The effect of one-month oral administration of naringenin (10, 20, and 40 mg/kg) and prednisolone (2 mg/kg) on peritoneal macrophage was compared in the first set of experiments. Separate evaluations were conducted on the effects of naringenin on in vivo and ex vivoT-helper (Th) lymphocyte responses and their subsets in mice immunized with ovalbumin (OVA). Animals challenged with OVA received oral doses of naringenin or prednisolone from two days prior to immunization to 28 days after immunization.Results: Naringenin and prednisolone increased macrophages' respiratory burst, and nitric oxide and interleukin (IL)-10 production while decreasing IL-12 production. Macrophages isolated from mice administered with 40 mg/kg naringenin had greater phagocytic potential than those isolated from mice administered with prednisolone. OVA-challenged mice treated with 40 mg/kg naringenin or prednisolone had decreased delayed-type hypersensitivity comparable to control mice. The splenocyte proliferation index was lower in the prednisolone-treated group than the naringenin-treated group, even at 40 mg/kg. In the splenocyte cultures, both agents decreased T-bet expression. Naringenin, in contrast to prednisolone, did not affect GATA3expression. The 40 mg/kg naringenin dose reduced RORγt more effectively than prednisolone.Conclusion: All these findings indicate the potential of naringenin as a modifying agent of immune responses. Consequently, naringenin may be beneficial in controlling some immunopathological conditions.